An analysis of stakeholders’ perceptions on urban water erosion in Windhoek, Namibia (Journal for Studies in Humanities and Social Sciences, 2019)
This study aimed at understanding the perceptions of stakeholders on urban water erosion in a dryland city - Windhoek (Namibia) - by interviewing 41 stakeholders using semi-structured questionnaires. Stakeholders’ perceptions were analysed by addressing their understanding of water erosion dynamics, their perceptions with regards to the causes and the seriousness of erosion damages, and their attitudes towards the responsibilities of urban erosion prevention and damages. The results indicated that there is less awareness of the process as a phenomenon; instead there is more awareness of erosion damages and the factors contributing to the damages. About 69% of the stakeholders considered erosion damages to be ranging from moderate to very serious. However, there were notable disparities between the private householders and public authority groups. The private householders and local authority sectors pointed fingers at each other as regards responsibility for erosion damage payments and for putting up prevention measures. The reluctance to take responsibility could undermine any effort to minimise erosion in urban areas and create a predicament for areas affected, especially in the informal settlements where land management is not carried out by the local authority and land is not owned by the occupants.